2021
DOI: 10.1242/dev.199460
|View full text |Cite
|
Sign up to set email alerts
|

Defective mesothelium and limited physical space are drivers of dysregulated lung development in a genetic model of congenital diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH) is a developmental disorder associated with diaphragm defects and lung hypoplasia. The etiology of CDH is complex and its clinical presentation is variable. We investigated the role of the pulmonary mesothelium in dysregulated lung growth noted in the Wt1 knockout mouse model of CDH. Loss of WT1 leads to intrafetal effusions, altered lung growth, and branching defects prior to normal closure of the diaphragm. We found significant differences in key genes; however, when Wt1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…A recent study reported similar findings and also reported an aberrant lung branching architecture already before closure of the diaphragm, when WT1 is expressed (32). When Wt1 −/− lungs were cultured ex vivo, lung branching was normal and any hypoplasia that had originated in vivo, was restored within 24 h ex vivo (32). Additional analyses showed that the space in the chest cavity-that is usually present for the lungs to grow-was nearly absent, explaining why culturing the lungs ex vivo without physical constraints recovered branching (32).…”
Section: Lung Mesotheliumsupporting
confidence: 65%
See 4 more Smart Citations
“…A recent study reported similar findings and also reported an aberrant lung branching architecture already before closure of the diaphragm, when WT1 is expressed (32). When Wt1 −/− lungs were cultured ex vivo, lung branching was normal and any hypoplasia that had originated in vivo, was restored within 24 h ex vivo (32). Additional analyses showed that the space in the chest cavity-that is usually present for the lungs to grow-was nearly absent, explaining why culturing the lungs ex vivo without physical constraints recovered branching (32).…”
Section: Lung Mesotheliumsupporting
confidence: 65%
“…Cano et al (24) showed that homozygous Wt1 knockout (Wt1 −/− ) mice had a CDH-like phenotype, abnormally fused lung lobes and reduced immunoreactivity for FGF9 in the pulmonary mesenchyme and mesothelium. A recent study reported similar findings and also reported an aberrant lung branching architecture already before closure of the diaphragm, when WT1 is expressed (32). When Wt1 −/− lungs were cultured ex vivo, lung branching was normal and any hypoplasia that had originated in vivo, was restored within 24 h ex vivo (32).…”
Section: Lung Mesotheliumsupporting
confidence: 63%
See 3 more Smart Citations